HUBUNGAN PERSONAL HIGIENE DENGAN PENYAKIT CACING (SOIL TRANSMITTED HELMINTH) PADA PEKERJA TANAMAN KOTA PEKANBARU - Siregar, Irham; Anita, Sofia (Jurnal Kajian Lingkungan, 2013)
Helminthes Disease is a kind of disease that mostly suffered within the community, although ithas been given little attention (neglected disease). The disease that slowly disturb human beinghealth, that may cause a permanent physical disability, decreasing of child intelligences, and atthe end can cause death. Behavior and conduct of the workers that is not in accordance withthe health principles is also can influence the workers’ health as like not using protection meanand lack of personal hygienic means like body protection, not in use of gloves, lack ofawareness in washing hands with antiseptic soaps, usage of the hygienic water so that hisbody could be infected by the eggs of worm. This observation is intended to recognize thepersonal hygienic relation means ( body protection, the habit of washing hands with antisepticsoaps and usage of the hygienic water ) with the Soil Transmitted Helminthes at City ofPekanbaru’s Plantation Workers. This observation is conducted at City of PekanbaruPlantation with 27 respondent samples where all inhabitants become samples by using analyticsurvey methods with cross sectional design. Data analysis is conducted in uni-variant and bi-variant with statistical trial of Chi-Square. Results of the observation shown variety inconnection with the existence of worms at City of Pekanbaru’s Plantation Workers based on Chi-Square trial, among others body protection means (Py = 0,024; OR = 0,08), the habit ofwashing hands with antiseptic soaps (Py = 0,024; OR = 0,08), while on using of hygienic water(Py = 0,115) is no relation with the existence of the worms. It is suggested to the decision makerin the government of Pekanbaru City, especially Regional Office of Ministry of Health,Cleanliness Service and City of Pekanbaru Park in providing body protection means like; shoes,gloves and antiseptic soaps in handling the effect that might caused by worm diseases.